Tuning the Photoluminescence of Germanium Nanocrystals through Surface Bound Functional Groups. (23rd December 2016) - Carolan, Darragh; Doyle, Hugh
Abstract : A room temperature, solution phase method for production of size monodisperse germanium nanocrystals (Ge NCs) terminated with different chemical functionalities (epoxy, acetate, amine, carboxylic acid, and alkyl) is reported. Ge NC photoluminescence spectra show that the emission can be tuned from the UV to the blue/green through choice of ligand.